Creativity, reality, and identity - Anisuzzaman (Dhaka, Bangladesh : International Centre for Bengal Studies, 1993)
Chiefly with reference to the history of the intellectual life of pre-partition Bengal and post-partition Bangladesh; includes political aspects.
Includes bibliographical references and index.
Keywords: Bengal (India) -- Intellectual life -- History